Comparative in Vitro Analysis of Azithromycin and Fosfomycin for Typhoid Treatment in Elderly Patients: Community Medicine Insights - Kiran Khan, Ata Ur Rehman, Syed Zaryab Ahmed, Amreen Liaquat, Lubna Farooq, Faraz Saleem, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Due to the careless use of antibiotics, resistance is growing daily, especially in third-world nations. When treating typhoid fever, a comparison of Azothimycin with fosfomycin may be helpful. Objective: To evaluate and compare the in vitro antibacterial efficacy, susceptibility, and resistance patterns of 15 µg azithromycin and 15 µg fosfomycin against Salmonella Typhi, isolates from elderly patients with uncomplicated typhoid fever. Materials and Methods: The Antibiotic sensitivity testing was performed using the Modified Kirby Bauer disc diffusion method and Blood culture examination was done using BACTEC 9240 system. We made 2 groups Group A and Group B, Grp A treated with Azithromycin while Grp B treated with Fosfomycin. Results: The resistance offered by Azithromycin was negligible 0 % in 50 to 60 years of age and 10% from 60 to 70 years of age respectively while the sensitivity rates were remarkable that is 55.6% in 50–60 years and 80.0% in 60–70 years. The resistance offered by Fosfomycin was extraordinary 72 % in 50 to 60 years of age and 93% from 60 to 70 years of age respectively while the sensitivity rates were Suboptimal that is 27% in 50–60 years and 6 % in 60–70 years. The p value of less than 0.05 of these comparisons was considered as significant. Conclusion: Azithromycin (15 µg) demonstrated superior in vitro efficacy and lower resistance than Fosfomycin in elderly patients with Salmonella Typhi, making it a strong treatment option for uncomplicated typhoid fever in high-resistance settings. Educating communities on typhoid prevention, symptoms, and treatment. Keywords: Salmonella typhi, Antimicrobial Susceptibility, Azithromycin, Fosfomycin